2015
DOI: 10.3390/proteomes3040411
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Study of Clavibacter Michiganensis Subsp. Michiganensis Culture Supernatants

Abstract: Clavibacter michiganensis, subsp. michiganensis is a Gram-positive plant pathogen infecting tomato (Solanum lycopersicum). Despite a considerable economic importance due to significant losses of infected plants and fruits, knowledge about virulence factors of C. michiganensis subsp. michiganensis and host-pathogen interactions on a molecular level are rather limited. In the study presented here, the proteome of culture supernatants from C. michiganensis subsp. michiganensis NCPPB382 was analyzed. In total, 187… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…For preparation of extracellular proteins, the cells were separated by centrifugation (25 min, 5000× g , 4 °C) and Complete EDTA-free protease inhibitor cocktail (Roche, Mannheim, Germany) was added to the supernatant to avoid proteolysis. To prevent contamination of extracellular proteins by cells or cell debris, the supernatant was centrifuged again (1 h, 7000× g , 4 °C) and subsequently filtered using 0.2 µm pore-size filters (Minisart, Sartorius, Göttingen, Germany) [ 27 ]. Proteins were precipitated under constant stirring by dropwise addition of trichloroacetic acid (10% w / v ) and incubation at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For preparation of extracellular proteins, the cells were separated by centrifugation (25 min, 5000× g , 4 °C) and Complete EDTA-free protease inhibitor cocktail (Roche, Mannheim, Germany) was added to the supernatant to avoid proteolysis. To prevent contamination of extracellular proteins by cells or cell debris, the supernatant was centrifuged again (1 h, 7000× g , 4 °C) and subsequently filtered using 0.2 µm pore-size filters (Minisart, Sartorius, Göttingen, Germany) [ 27 ]. Proteins were precipitated under constant stirring by dropwise addition of trichloroacetic acid (10% w / v ) and incubation at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Mass spectrometric analyses by nanoLC-MS/MS were carried out as described [ 27 ]. In short, resulting peptides (approx.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two plasmids, pCM1 and pCM2, were also identified in Cmm 382 and are necessary for full virulence . Subsequent omics analyses of Cmm have validated the annotated genome and provided evidence for expression of putative virulence genes . A recent comparative genomic study of 16 pathogenic Cmm isolates identified 13 core Sec‐dependent secreted proteins .…”
Section: Table Of Novel Cmm382 and Plasmid Genes Identified In This Smentioning
confidence: 97%
“…Since we are interested in the analysis of pathogenicity determinants of corynebacteria [ 24 , 25 , 26 , 27 ] and different aspects of bacterial proteomics [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], we started a characterization of the cellular and extracellular proteome of C. silvaticum isolate W25, which is presented here. In total, 1305 proteins were identified out of 2013 proteins encoded by the W25 genome sequence including a number of putative virulence factors such as phospholipase D and sialidase.…”
Section: Introductionmentioning
confidence: 99%